2014
DOI: 10.1111/bjh.13158
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of anti‐D alloimmunization following D+ platelet transfusion: the Anti‐D Alloimmunization after D‐incompatible Platelet Transfusions (ADAPT) study

Abstract: Summary The reported frequency of D alloimmunization in D- recipients after transfusion of D+ platelets varies. This study was designed to determine the frequency of D alloimmunization, previously reported to be an average of 5%±2%. A primary anti-D immune response was defined as the detection of anti-D ≥28 days following the first D+ platelet transfusion. Data were collected on 485 D- recipients of D+ platelets in 11 centres between 2010-2012. Their median age was 60 (range 2-100) years. Diagnoses included: h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 37 publications
6
69
1
Order By: Relevance
“…Data analyzed of the patients identified to have obviously been alloimmunized through PC transfusions included: age, gender, ABO blood group and Rh phenotype, main diagnoses, immunosuppressive drugs, transfusion history (Inselspital only), and date of alloantibody detection [7]. Transfusion history included every RBC and PC unit transfusion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data analyzed of the patients identified to have obviously been alloimmunized through PC transfusions included: age, gender, ABO blood group and Rh phenotype, main diagnoses, immunosuppressive drugs, transfusion history (Inselspital only), and date of alloantibody detection [7]. Transfusion history included every RBC and PC unit transfusion.…”
Section: Methodsmentioning
confidence: 99%
“…Since the introduction of mandatory universal pathogen inactivation of all PC in 2011 [2], AP-PC and BC-PC are considered clinically equivalent. However, some differences exist between both types of PC, such as the extent of residual contaminating red blood cells (RBC), which has been shown to be considerably lower for AP-PC (0.00017-0.009 ml) compared to BC-PC (0.036-0.59 ml) [3,4,5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have focused our study on this subset of patients (only young women) because of the potential serious consequences of anti-D alloimmunization in future pregnancies (HDN). Previous studies reported an anti-D alloimmunization rate ranging from 0 to 19% in patients suffering from oncologic diseases and therefore immunosuppressed [5,9,12,13,14,15,16,17,18,19,20]. Lack of anti-D immunization is the most founded result in studies with small numbers of immunosuppressed patients [9,13,17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-D alloimmunization can therefore occur when platelets from RhD-positive donors are transfused to RhD-negative patients. Various studies of RhD-negative recipients receiving RhD-positive platelet transfusions reported an incidence of 0-19% RhD alloimmunization in cancer patients [5,6,7,8]. Prevention of anti-D alloimmunization by administering Rh immunoglobulin is a well-established practice for RhD-negative pregnant women to prevent hemolytic disease of the newborn (HDN).…”
Section: Introductionmentioning
confidence: 99%